Branding en el posicionamiento de la productora de mariscos Punacuario S.A en la provincia, El Oro - Velasco Solorzano, Ronny Patricio (2023)
This research focuses on analyzing the situation of Punacuario. It is a shrimp company located in the El Oro Province, within the Ecuadorian aquaculture industry and in a province renowned for the quality of its products. Despite experiencing financial growth, the company faces challenges related to its market recognition, competitive position, and price competition. The study reveals that a lack of understanding in areas of branding and marketing has led to limited positioning and the absence of a defined target audience. The main purpose of the branding proposal is to strengthen the organizational culture by delineating its distinctive attributes and values, and to present a strong image to consumers through multiple communication channels. The ultimate goal is to reinforce the company's presence in the market, diversify its sources of income, and cultivate customer loyalty. The aim is to implement branding strategies that stimulate sustainable growth and enhance the company's position in the local market.